Effects of grape pomace supplementation on the diet of lactating ewes as compared to vitamin E on the meat shelf life of suckling lambs. (February 2022) - Vieira, C.; Guerra-Rivas, C.; Martínez, B.; Rubio, B.; Manso, T.
Abstract: Forty-eight Churra ewes and their suckling lambs were assigned to four dietary treatments: control (CTRL), VIT-E (500 mg kg-1 TMR vitamin E), GP-5 (5% grape pomace) and GP-10 (10% grape pomace). After slaughter (11.5 kg live weight), longissimus muscle of lambs was sliced, packaged under modified atmosphere (80, 20%/O 2:CO 2) and stored in retail conditions. At each sampling point (0, 3, 7, 10, 14 days), microbiological, physicochemical and sensory characteristics were analysed. Vitamin E and GP-5 were found to be effective ( p < 0.05) at preventing enterobacteria growth as of day 10. After day 10, vitamin E and grape pomace in the ewe's supplementation reduced metmyoglobin ( p < 0.05) lipid oxidation (p < 0.05) and sensory spoilage throughout the storage period. An effect of the grape pomace dosage was observed, with the supplementation at 5% being more effective. Therefore, we can conclude that grape pomace was just as effective as vitamin E in preventing spoilage during retail storage. HIGHLIGHTS: Addition VIT-E and grape pomace to ewe diet affects shelf life of suckling lamb meat packaged and stored in retail conditions. Ewes fed VIT-E and grape pomace delayed myoglobin, lipid oxidation and sensory spoilage of suckling lamb meat during storage. Grape pomace was as effective as vitamin E in extending the shelf life of lamb meat. Supplementation of 5% grape pomace in ewe diets was more effective at extending shelf life of suckling lamb meat than 10%